2007
DOI: 10.1016/j.joep.2007.02.001
|View full text |Cite
|
Sign up to set email alerts
|

Does watching TV make us happy?

Abstract: Watching TV is a major human activity. Because of its immediate benefits at negligible immediate marginal costs it is for many people tempting to view TV rather than to pursue more engaging activities. As a consequence, individuals with incomplete control over, and foresight into, their own behavior watch more TV than they consider optimal for themselves and their well-being is lower than what could be achieved. We find that heavy TV viewers, and in particular those with significant opportunity cost of time, r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
77
0
3

Year Published

2010
2010
2020
2020

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 192 publications
(86 citation statements)
references
References 34 publications
1
77
0
3
Order By: Relevance
“…People who, on average, engage in greater sedentary behavior (operationalized as TV viewing) also tend to experience lower SWL compared with people who are less sedentary (Depp, Schkade, Thompson, & Jeste, 2010;Frey, Benesch, & Stutzer, 2007).…”
Section: Satisfaction With Life and Sedentary Behaviormentioning
confidence: 99%
See 2 more Smart Citations
“…People who, on average, engage in greater sedentary behavior (operationalized as TV viewing) also tend to experience lower SWL compared with people who are less sedentary (Depp, Schkade, Thompson, & Jeste, 2010;Frey, Benesch, & Stutzer, 2007).…”
Section: Satisfaction With Life and Sedentary Behaviormentioning
confidence: 99%
“…Results indicated that physical activity and sedentary behavior had additive within-person influences on SWL in this study. The independent effects of sedentary behavior on physiological outcomes, regardless of physical activity have been documented (e.g., Healy et al, 2011;Proper et al, 2011;Thorp et al, 2011); however, this is one of the few studies to document the negative association between sedentary behavior and a global indicator of well-being irrespective of physical activity (Depp et al, 2010;Frey et al, 2007). Yet, unlike previous studies that only examined the link between sedentary behavior and SWL at the between-person level (Depp et al, 2010;Frey et al, 2007), this study simultaneously examined associations between physical activity and SWL at both the between-and within-person level, revealing a significant withinperson, but not between-person, association.…”
mentioning
confidence: 95%
See 1 more Smart Citation
“…Así, entre los estudios recientes desarrollados a partir de datos internacionales, podemos destacar los realizados por Frey et al (2007), Bruni y Stanca (2008) o Kataria y Regner (2011). Para el caso de España, cabe mencionar el trabajo de Cuñado y Pérez de Gracia (2012), en el que se confirma la expectativa de que cuanto mayor es el número de horas que un individuo ve la televisión, menor es su felicidad.…”
Section: Introductionunclassified
“…Otra explicación menos drástica es la presencia de problemas de autocontrol (Stutzer y Frey, 2006;Benesch et al, 2010), de forma que la voluntad es vencida por la pereza debido al escaso coste inmediato que implica ver la televisión. En la decisión de ver la televisión, los individuos pueden dejarse llevar en el momento por factores a corto plazo como el entretenimiento o el descanso, sin ser capaces de predecir los efectos negativos futuros (Frey et al, 2007).…”
Section: Introductionunclassified